THE SYSTEM OF CIVIL LEGAL METHODS OF PROTECTION OF THE PROPERTY RIGHTS OF THE STATE - Kanapyanova Гульмира Танирбергеновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In article the author considers system of civil ways of protection of property rights of the state, as obligations and legal and proprietary ways. Attempt on differentiation of separate types of proprietary ways of protection of property rights of the state is also made.